Comparison of points of departure between subchronic and chronic toxicity studies on food additives, food contaminants and natural food constituents. (December 2020) - Guth, Sabine; Roth, Angelika; Engeli, Barbara; Lachenmeier, Dirk W.; Cartus, Alexander T.; Hüser, Stephanie; Baum, Matthias; Diel, Patrick; Eisenbrand, Gerhard; Hengstler, Jan G.; Humpf, Hans-Ulrich; Joost, Hans-Georg; et al.
Abstract: It was generally accepted as a default assumption that No-Observed-Adverse-Effect Levels (NOAELs) or Lowest-Observed-Adverse-Effect Levels (LOAELs) in long-term toxicity studies are lower than in short-term ones, i.e. the toxic potency increases with prolonged exposure duration. Recent studies on pesticides and industrial chemicals reported that subacute, subchronic or chronic NOAELs/LOAELs are similar when study design factors are appropriately considered. We investigated whether these findings also apply to certain food constituents. After reviewing subchronic and chronic toxicity studies on more than 100 compounds, a total of 32 compounds could be included in the analysis. Geometric mean (GM) values of subchronic vs. chronic NOAEL or LOAEL ratios ranged from 1.0 to 2.0, with a geometric standard deviation from 2.2 to 4.2, which is consistent with data reported in the literature. While for many of the investigated compounds the ratio is around 1 – suggesting that health-based guidance values could appropriately be derived from subchronic toxicity studies – our study also identified some substances with higher ratios leading to a GM of around 2. The EFSA Scientific Committee suggested to apply an uncertainty factor of 2 to extrapolate from subchronic to chronic studies and, as a precautionary approach, we concur with this suggestion. Highlights: Toxicity data on > 100 compounds present in food were reviewed. Points of departure (PoD) from subchronic vs. chronic studies were compared. Geometric mean values of subchronic vs. chronic PoD ratios ranged from 1.0 to 2.0 Health-based guidance values may be derived from subchronic toxicity studies. Data support use of a factor of 2 to extrapolate from subchronic to chronic studies.